Leitura de contos e criação escrita: um convite à fruição literária - Paz, Maria Conceição Oliveira da (2024)
This study aims to propose teaching strategies through the reading and analysis of literary short stories, with a view to expanding access to literature for 8th grade elementary school students. Furthermore, it aims to develop humanization in students through the practice of studying the short story genre, with the aim of leading them to enjoy literary texts. To this end, the following theoretical references are taken: i) regarding the notions of reading comprehension: Solé (1998) and Leffa (2012); ii) regarding a procedural approach to written production: Passareli (2012); iii) as support for discussions focused on the perception of literature as an instrument of humanization: Candido (2011), Barthes (2015) and Todorov (2009); and iv) concerning the debate inherent to the definition and social function of the short story genre: Cortázar (2006), Gotlib (2004), Piglia (2004) and Moisés (2006). In methodological terms, the work is proposed with a didactic sequence, consisting of four modules, organized into twelve classes, so as to allow students to read short stories by different authors and themes so that, at the end, they feel motivated to produce literary reviews to be publicized in the school environment. Taking into account the proposal elaborated for the research and its execution, it is possible to say that this work obtained a significant result, since, during the classes, it was noticed that the students were enchanted by literary texts, as they assumed a critical attitude towards the short stories studied, along with a reflection on reality. Furthermore, with the aim of socializing the results of this project with Portuguese language teachers, a Pedagogical Notebook is presented. It explicitly presents a feasible methodology for serving the final years of elementary school, allowing language teachers to make adjustments to the proposal, considering the reality, context and learning level of the classes. In a broad sense, the idea is to collaborate with possibilities of redefining the work with the short story genre in basic education, since literature needs to be part of the students' school universe and the contexts of their lives.